Legitimization imperative: the production of crime statistics in Guangzhou, China : Jianhua Xu - Xu, Jianhua (The British journal of criminology, 2018)
Although an authoritarian regime is often assumed to manipulate its various statistics for political needs and to maintain its legitimacy, we know little about how such manipulation is accomplished and under what circumstances. Using data collected from yearly published official crime reports, a unique source for crime victim surveys, interviews with the police and detailed ethnographic work in Guangzhou city, this paper demonstrates how the manufacturing of official crime statics serves to legitimize the authoritarian regime in China. In particular, I examine the myth of the ‘great crime decline’ in the first decade of 21st century when official crime statistics declined by more than two-thirds in the city and argue that the decrease is a result of statistical manipulation instead of a reflection of the actual crime situation. I argue that, compared with Western democracies, crime statistics should be more fully understood as part of a legitimization apparatus in China.